Statistical Analysis of Self-Weight Penetration and Pile Running for Large Diameter Monopiles in Offshore Wind Farm - Hongqing WANG; Wei SUN; Donghua LIU; Hao REN; Dongsheng TANG; Hui FANG (南方能源建设, 2023)
[Introduction] This paper adoptes the methods based on parametric study and CPT in-situ test for analysis and calculation, the preliminary analysis is carried out according to the actual construction data. By doing this, the self-weight penetration of monopiles can be better and faster predicted and the risks in monopile installation are significantly reduced. [Method] Modified the design input parameters by API recommended pile capacity theory, combined with error analysis, the predicted self-weight penetration was compared to the real data on site. [Result] The analysis results show that there is a great difference in prediction of self-weight penetration due to the different reduction strength coefficient \begin{document}$ S_{r} $\end{document} in the process of calculating clay self-weight penetration and pile running analysis. At the same time, the selection of reduction strength coefficient is different between the self-weight penetration and pile running process. [Conclusion] Through comparative analysis, the value range of clay strength reduction coefficient \begin{document}$ S_{r} $\end{document} of Guangdong sea area is obtained, which can provide a design reference for the following offshore pile penetration operations. It's also proved that the CPT can be used to better predict self-weight penetration and pile running phenomenon.